High frequency of contact allergy to implant and bone cement components, in particular gentamicin, in cemented arthroplasty with complications: usefulness of late patch test reading - Thomas, Benjamin; Kulichova, Daniela; Wolf, Ronald; Summer, Burkhard; Mahler, Vera; Thomas, Peter (Contact Dermatitis, 2015)
Arthroplasty patients with complications may be sensitized to implant components.To quantify patch test reactions to implant materials in aseptic cemented arthroplasty patients with complications, and to evaluate the benefit of late patch test reading at D6.Analyses of patch test reactions to baseline series and bone cement components and of the questionnaire-aided histories of 250 consecutive patients with suspected implant allergy were performed. Patch tests were read at D2, D3, and D6.There were 187 positive reactions to the 29 allergens of the baseline series, and 52 to the seven allergens of the bone cement series. Forty-nine of 250 patients reacted to the bone cement series. In contrast to 'early allergens' such as fragrance mix, late reading at D6 increased the number of positive reactions by 11/32 for nickel, 1/5 for cobalt, and 2/4 for chromium. With bone cement components, most reactions were to gentamicin (25 of 250 patients), and 17 of 25 appeared only at D6.Late reading is useful for patch tests with metals and bone cement components. With only D2/D3 readings, 32 reactions to nickel, cobalt, chromium and bone cement components would have been missed. This underlines the utility of late reading in general and in complicated cemented arthroplasty patients, given the unexpectedly high number of gentamicin reactions.
EVALuna2:19557